Perceptions of Turkish University Students about the Role of Teacher as a Mediator and Mediated Learning Experience - Ertit, Abdullah (The Literacy Trek, 2017)
This study explores the perceptions of university students about Feuerstein’s mediated learning experience (MLE) and the role of teacher as a mediator. In this qualitative study, students from 4 departments at an education faculty in a state university in Turkey were grouped as experimental and control group and received intervention in English course based on mediated learning experience and social constructivist theory. At the end of the intervention, a total of 20 students from two different departments in the experimental group were interviewed face-to-face and the data were analyzed through content analysis. Based on the findings of the study, students reported that the role of teacher as a mediator facilitated their learning process in a positive way by increasing their motivation, self-confidence, autonomy and willingness to communicate by enabling them to have a better interaction among group and class members as their friends. Findings also imply the fact that although the education system in Turkey is designed upon the principles of constructivist approach since the introduction of the 2006 curriculum reform, students had not been exposed to constructivism based classroom practices prior to the intervention applied for this study.
Keywords: Mediation; Mediated Learning Experience; Teacher As A Mediator; Language Learning